2022
DOI: 10.3389/fimmu.2022.894206
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of a Shigella 2aT32-Based Vaccine Expressing UreB-HspA Fusion Antigen With and Without Parenteral rUreB-HspA Boost Confers Protection Against Helicobacter pylori in Mice Model

Abstract: Helicobacter pylori (H. pylori) is a gram-negative pathogen classified as a class I carcinogen. The H. pylori urease B subunit (UreB) and heat shock protein A (HspA) are two important vaccine candidate antigens. In this study, we evaluated the immunogenicity and immunoprotective effect of the attenuated Shigella vector vaccine SH02 expressing the UreB-HspA fusion protein of H. pylori in a mouse model. Oral SH02 with or without subcutaneous injection of rUreB-HspA induced antigen-specific serum IgG, mucosal sIg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Typhimurium Δ rfbP Δ fliC Δ fljB Δ ompA mutant strain successfully elicited strong humoral and mucosal immunity in mice, and markedly increased IgG and IgA levels. IFN-γ and IL-17 have been proven to be vital in immunity against H. pylori infection [ 24 ], and CD154 expression on the surface of activated CD4 + T cells determines the degree of differentiation of CD4 + T cells into Th1 and Th17 cells after immunization [ 25 ]. Our data showed that the constructed vaccine induced significant increases in CD4 + T cells relevant to preventing H. pylori infection and related cytokines IFN-γ and IL-17 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium Δ rfbP Δ fliC Δ fljB Δ ompA mutant strain successfully elicited strong humoral and mucosal immunity in mice, and markedly increased IgG and IgA levels. IFN-γ and IL-17 have been proven to be vital in immunity against H. pylori infection [ 24 ], and CD154 expression on the surface of activated CD4 + T cells determines the degree of differentiation of CD4 + T cells into Th1 and Th17 cells after immunization [ 25 ]. Our data showed that the constructed vaccine induced significant increases in CD4 + T cells relevant to preventing H. pylori infection and related cytokines IFN-γ and IL-17 levels.…”
Section: Discussionmentioning
confidence: 99%
“…A lymphocyte proliferation assay was conducted according to the revised version of a previously method [ 25 , 26 ]. Single-cell suspensions (4 × 10 5 /well) were seeded in plates containing RPMI 1640 medium containing 10% (v/v) fetal bovine serum, 1% (v/v) penicillin–streptomycin (Thermo Fisher Scientific), and 20 µg/mL rPA at 37 °C and under 5% CO 2 for 72 h. During the final four hours of incubation, 20 µL CCK-8 solution was added.…”
Section: Methodsmentioning
confidence: 99%
“…The basic immunization consisted of either three oral administrations or two oral immunizations, followed by a third immunization involving a subcutaneous injection of rUreB-HspA for immune enhancement. Both approaches significantly reduced H. pylori colonization and gastric inflammation in mice ( Zhang et al, 2022 ).…”
Section: New Approachesmentioning
confidence: 99%